PERHITUNGAN ENERGI SOLAR PHOTOVOLTAIC DI WILAYAH KABUPATEN NIAS DAN KABUPATEN MENTAWAI DENGAN MENGGUNAKAN METODE PROBABILISTIK - Boy Harefa; Bambang Widodo; Stepanus stepanus; Robinson Purba (Prodi Teknik Elektro FT UKI, 2020)
This paper discusess the calculation of solar photovoltaic energy using a probabilistic approach in Nias and Mentawai districts. The application used is the @RISK Risk Analysis Project Model. In this research, the calculated random variable is the average temperature, the length of sunshine per month and solar radiation according to the regional zone. These three variables are fluctuating, so that the approach of each varianble uses a uniform distirbution function. From the three variables, it can be calculated that the energy generated by solar photovoltaic with a capacity of 100 Wp in Nias Regency is 21.062,57 kWh in one year with a probability of 55% and a capacity factor of 24,04%. Meanwhile, in Mentawai District, the same solar photovoltaic capacity of 100 Wp produces 19.249,47 kWh of energy with a probability of 50% and a capacity factor of 21,97%. From the results of this study it can be seen that the average temperature, duration of solar radiation and solar radiation can determine the electrical energy that can be generated by solar radiation can determine the electrical energy that can be generated by solar photovoltaic